New business in India : the 21st century opportunity - Davies, Paul (Paul J.) (World Scientific series on 21st century business ;, 2008)
New Business in India is focused on how to enter the Indian domestic market, which is currently growing at nearly 10% per annum. The book is important as it is based on first-hand experience and real insights into the market in India, establishing a company and business, and developing the marketing and sales programme for both business-to-business (B2B) and business-to-consumer (B2C) companies. Serving as a comprehensive introduction to entering the market, this book, in short, is able to take business planners and developers working in both large and small companies through the processes the.